Geotecnologias aplicadas na análise da piscicultura das sub-bacias hidrográficas dos rios São Francisco e São Francisco Falso, no oeste do Paraná - Silva, Antonio Francisco Campanha da (2024)
The assessment of morphometric indices in river basins serves as a valuable tool for planning sustainable production and environmental conservation. The identification, quantification, and mapping of excavated fish farming ponds in the sub-basins of the San Francisco and San Francisco Falso Rivers also aim to contribute to the development of future research on mountain aquaculture. To classify the areas, a Geographic Information System (GIS) and data from a Digital Elevation Model (DEM) were used, along with land use and soil type data. Analyses were conducted using geomorphological, pedological, hypsometric, slope, hydrological, and land use maps. The San Francisco (SF) and San Francisco Falso Rivers are sub-basins with elongated drainage networks and low flood risk. Their structure supports the development of fish farming activities in the region. These rivers are situated in a landscape characterized by altitudes ranging from 219 to 763 meters. The predominant terrain in the region is gently undulating, which influences the drainage dynamics and the formation of floodplains along the watercourses. Additionally, the dominant soil type in the area is Red Latosol, a deep and highly weathered soil with good drainage and chemical characteristics that can influence both vegetation and productive activities in the region. Tilapia is the most commonly farmed species in the sub-basins, establishing the region as a hub for aquaculture production. This development is driven by the organization of the local production chain and the industrialization of fish processing. In the study area, fish farming is carried out in small excavated ponds, ranging in size from 300 to 3,000 m². In the São Francisco River, 64.70% of the ponds are located at altitudes between 300 and 600 meters. In the São Francisco Falso River, 55.90% of the production structures are found in areas with altitudes between 0 and 300 meters. These distribution patterns reflect the geomorphological characteristics of the sub-basins and their influence on aquaculture activity. The use of geoprocessing tools, such as GIS and DEM, enabled a detailed assessment of land use and environmental factors impacting fish farming. These data are essential for the sustainable planning of the activity, contributing to the mitigation of environmental impacts and the advancement of research focused on aquaculture in sub-basin regions.